The Effect of Six Weeks of High-Intensity Interval Training with and without Coenzyme Q10 Supplementation on Bench Press and Squat Strength in Competitive Male Bodybuilders - Javad Almasi; Mohammad Mahdi Shabazbigian (Biyumikānīk-i varzishī)
Objective Resistance training can be performed using external weights or body weight. It induces muscle tension, ultimately leading to increases in contractile proteins, muscle cross-sectional area, anaerobic power, speed, strength, muscular endurance, and motor function—all of which play key roles in enhancing athletic performance. This study aimed to investigate the effect of six weeks of high-intensity interval training (HIIT), with and without coenzyme Q10 supplementation, on the muscular strength of male bodybuilders in Hamadan. Methods This semi-experimental study involved a statistical population of 200 male bodybuilders in Hamadan. Thirty participants (mean age: 23.3 ± 0.4 years; height: 172 ± 6 cm; weight: 76 ± 2.6 kg), with no history of Q10 supplementation or HIIT during the previous six months, were randomly and voluntarily selected and assigned to two groups of 15. Ethical considerations were addressed using a health screening questionnaire and informed consent form. The experimental group underwent six weeks of HIIT combined with coenzyme Q10 supplementation, while the control group performed the same HIIT protocol with a placebo supplement of identical appearance and dosage. Muscular strength was assessed using Impulse fitness machines (manufactured in China), and one-repetition maximum (1RM) was calculated. Data were analyzed using the Shapiro–Wilk test and univariate and multivariate analysis of covariance (ANCOVA) via SPSS version 25. Results The results indicated significant improvements in muscular strength in both groups, with greater gains observed in the group receiving CoQ10 supplementation. In the bench press, 55% of the variance in post-test strength was attributed to the intervention (F = 33.58, p < 0.001, η² = 0.554), and in the squat, this effect reached 80% (F = 107.22, p < 0.001, η² = 0.799). Conclusion Six weeks of high-intensity interval training significantly improved upper and lower body strength in male bodybuilders. The combination of HIIT and CoQ10 supplementation was more effective than HIIT alone. These findings suggest that CoQ10 may serve as a beneficial supplement for enhancing muscular performance and mitigating fatigue in strength-based training programs.